Kepribadian Dan Emosi Tokoh Saka Dalam Novel Egosentris Karya Syahid Muhammad : Kajian Psikologi Sastra - Mar Atussholihah Tri Haryani; Safira Yunita Rahmawati; Eva Dwi Kurniawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research discusses the personality and emotions of the character Saka in the novel Egocentric by Syahid Muhammad. The aim of the research is to explain an in-depth and detailed understanding of the personality structure and emotional classification of the Saka character. This research is a qualitative descriptive study. The approach used is literary psychology using Sigmund Freud's personality theory and David Krech's emotional classification theory. The data for this research is a quote from the novel Egocentric by Syahid Muhammad. The data collection method in this research uses the literature study method. The results and discussion show that Saka's character has an id, ego and superego personality structure and shows Saka's emotional classification.